2021
DOI: 10.3390/s21196632
|View full text |Cite
|
Sign up to set email alerts
|

On Measuring Implant Fixation Stability in ACL Reconstruction

Abstract: Numerous methods and devices are available for implant fixation in anterior cruciate ligament (ACL) reconstruction. Biomechanical data indicate high variability in fixation stability across different devices. This study aims to provide a better insight into measuring the structural characteristics and mechanical behavior of ACL implant fixations. Fourteen human tibial specimens with reconstructed ACLs were subjected to progressively increasing dynamic loading until failure. The motions of the tibia, the proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Since any ACL graft must be considered as hyperelastic, the slippage of the graft and corresponding stiffness of the fixation are potentially different from the values generated by the displacement of the load frame. A recent study ( Benca et al, 2021 ) has shown that during cyclic loading the machine-measured displacement is mostly a result of graft strain. It was further reported that the machine-measured displacement correlated with graft slippage allowing only for some qualitative evaluation between different fixation devices but stiffness was overall underestimated by up to 400% ( Benca et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since any ACL graft must be considered as hyperelastic, the slippage of the graft and corresponding stiffness of the fixation are potentially different from the values generated by the displacement of the load frame. A recent study ( Benca et al, 2021 ) has shown that during cyclic loading the machine-measured displacement is mostly a result of graft strain. It was further reported that the machine-measured displacement correlated with graft slippage allowing only for some qualitative evaluation between different fixation devices but stiffness was overall underestimated by up to 400% ( Benca et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study ( Benca et al, 2021 ) has shown that during cyclic loading the machine-measured displacement is mostly a result of graft strain. It was further reported that the machine-measured displacement correlated with graft slippage allowing only for some qualitative evaluation between different fixation devices but stiffness was overall underestimated by up to 400% ( Benca et al, 2021 ). Interestingly, the slippage onset, defined as an initial displacement of at least 0.1 mm, occurs already at relatively low load levels in both implant groups (64.5 and 56.0 N for the interference screw and Shark Screw ACL, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations